Investigation of the role of sleep and physical activity risk for chronic disease prevalence in older Irish adults - Romero-Ortuno, Roman; Scarlett, Siobhan; Hernndez, Belinda; Kenny, Rose; Reilly, Richard (My University, 2022)
Background: Chronic diseases are the leading cause of death worldwide. Many of these diseases have modifiable risk factors, including physical activity and sleep, and may be preventable. This study investigated independent asso‑ ciations of physical activity and sleep with eight common chronic illnesses. Methods: Data were from waves 1, 3 and 5 of The Irish Longitudinal Study on Ageing (n = 5,680). Inverse probabil‑ ity weighted general estimating equations were used to examine longitudinal lifetime prevalence and cumulative incidence of self‑reported conditions. Results: Sleep problems were significantly associated with increased odds of incident and prevalent arthritis and angina. Additionally sleep problems were associated with higher odds of lifetime prevalence of hypertension and diabetes. Physical activity was negatively associated incident osteoporosis and respiratory diseases and negatively associated with lifetime prevalence of hypertension, high cholesterol and diabetes. Conclusions: Worse sleep quality and lower physical activity were associated with higher odds of chronic diseases. Interventions to improve sleep and physical activity may improve health outcome
PUBLISHED
Keywords: Multimorbidity; Physical activity; Sleep; Chronic illness; Ageing; Age-related disability; Mental Health/Psychosocial disability; Health; Third age/ageing